Outcomes associated with early removal versus retention of peripherally inserted central catheters after diagnosis of catheter-associated infections in neonates. (16th December 2016) - Deshpande, Poorva; Jain, Amish; Shah, Prakesh S.
Abstract: Objective : To compare clinical outcomes and hospital resource utilization of infants who had peripherally inserted central catheters removed early versus retained following diagnosis of central line-associated bloodstream infection. Study Design : In a single centre retrospective cohort study, we compared outcomes of infants who had peripherally inserted central catheters removed early versus retained after diagnosis of central line-associated bloodstream infection. Mortality, cardio-respiratory deterioration, use of blood products and antibiotics were compared between groups. Results : Over a 10-year period, of the 119 eligible infants, 38 had peripherally inserted central catheters removed early and 81 had catheters retained after diagnosis of central line-associated bloodstream infection. Baseline demographics, illness severity at onset of sepsis and distribution of organisms were similar between the groups. Infants in "catheter–retained" group required longer antibiotic usage (17 ± 9 versus 13 ± 6 days; p  = 0.025) and more frequent sequential positive blood cultures [31/81 (47%) versus 8/38 (22%), p  = 0.014). Infants with Gram-negative bacteremia demonstrated higher mortality when catheters were retained [43% (9/21) versus 7% (1/14); p  = 0.028]. Conclusions : Retaining peripherally inserted central catheters after diagnosis of central line-associated bloodstream infection was associated with longer duration of bacteremia and prolonged exposure to systemic antibiotics as well as increased mortality in Gram-negative bacteremia.